Ingredientes ativos nos atendimentos dos centros de atenção psicossociais (CAPS) na perspectiva de cuidadores de crianças atendidas: uma teoria fundamentada em dados - Nalini, Karine Dutra Mesquita (2020)
This master's dissertation searched from the qualitative research method, whose reference was the Grounded Theory Analysis,identify which are the active ingredients of the Psychosocial Care Centers from the perspective of children's caregivers attended. 32 caregivers who were in attendance between 2017 to 2019, with children from 4 to 12 years old, had participated the research. Two types of Psychosocial Care Centers were part of the sample: CAPSi and CAPS-I. The Goiás counties: Goiânia, Aparecida de Goiânia, Anápolis, Ipameri and Catalão were visited. Emerging data allowed the creation of a Conceptual Scheme where were identified: (a) - the conditions that led to the search for care; (b) - the Active Ingredients; (c) - the Informal Relations/Interpersonal's moderators; and (d) - Effects of Psychosocial Care. As regards the active ingredients, from the tension between promoter and limiting factors of mental health care,two functional axes emerged: 1) - Formal Administrative/Political Relations in the CAPS and 2) - The Informal/Interpersonal Relations (Users and Health Care Team). With the proposed model, It is expected that services focused in Childish Mental Health Care, that could be used as an instrument that will assist the technical teams, and it managers to verify if in their service programs,the active ingredients, here emerging, are recognized between their actions and interactions